An unusual case of tuberous sclerosis incidentally discovered in adulthood: case report and review of the literature. (December 2018) - Ferrara, Dolores; Vallone, Gianfranco; Tedeschi, Enrico; Ponsiglione, Andrea; Stanzione, Arnaldo; Pisani, Antonio; Imbriaco, Massimo
Tuberous sclerosis (TS) is a relatively rare multi-organ disorder generally diagnosed in infancy and described as a clinical triad of sebaceous adenoma, mental retardation, and seizures. Angiomyolipoma (AML) is the most common benign renal tumor usually found incidentally as a solitary small echogenic lesion on grayscale ultrasound. Less commonly, it is part of the TS complex and is seen as multiple lesions in both kidneys. We describe an unusual case of TS incidentally diagnosed in a 37-year-old female patient with several and bilateral renal AMLs and a single cortical–subcortical tuber in the right parieto-occipital cerebral lobe.